A HAJJ PSYCHOLOGY TRAINING MODULE DESIGNED TO IMPROVE THE EMOTIONAL INTELLIGENCE OF PROSPECTIVE PILGRIMS - Razak, Ahmad; Yasser Mansyur, Ahmad; Thalib, Tarmizi; Muhammadong (Jurnal Adabiyah, 2022)
The study aimed to design a Hajj psychology training module. The research method was research and development (R&D). The stages of the research were analyzing the needs, developing the module, having expert validation, and having responses from prospective pilgrims. Five aspects had been validated for feasibility, namely a) basic competencies and indicators; b) content of the material; c) training methods; d) language, and; e) development area. The results of expert validation tests and responses from prospective pilgrims indicated that the Hajj psychology training module was in the feasible category to use. ملخص الملخص: تهدف هذه الدراسة إلى تصميم وحدة تدريبية في علم نفس الحج. هذا النوع من البحث هو البحث والتطوير (البحث والتطوير). مراحل البحث هي: تحليل الاحتياجات ، تصميم الوحدة ، التحقق من صحة الخبراء ، الحجاج المرتقبون. هناك خمسة جوانب تم التحقق من صحتها من أجل الجدوى ، وهي أ) الكفاءات والمؤشرات الأساسية ؛ ب) محتوى المادة ؛ ج) طرق التدريب. د) اللغة و ؛ هـ) منطقة التطوير. تشير نتائج اختبار التحقق من صحة الخبراء وكذلك الحجاج المحتملين إلى أن وحدة التدريب على علم نفس الحج في فئة ذات جدوى ممكنة.